Geochemical characteristics and sedimentary environment of black mudstone in the early Carboniferous Dawuba Formation in the Middle and Upper Yangtze region - Zhang, Haiquan; Zhang, Qian; Zhou, Yexin; Lan, Baofeng; Feng, Xintao; Chen, Yi; Yu, Qian; Cheng, Jinxiang; Men, Yupeng; Zhao, Ankun (Frontiers in Earth Science, 2023)
To further study the sedimentary environment of the black mudstone in the early Carboniferous Dawuba Formation in the Middle and Upper Yangtze regions and support regional shale gas exploration and related research, the major and trace elements of the Dawuba Formation in Well CY1, located in deep water shelf facies, were tested and analyzed. The results show that the study area contains mainly continental margin deposits affected by hydrothermal deposition, and they are rich in organic matter and have high primary productivity. The parent rocks are mainly acidic rocks, such as felsic igneous rocks, granites and some sedimentary rocks. And the provenance is mainly provided by acidic igneous rocks of the JiangnanPaleouplift. An ICV<1 and high CIA and Th/U values indicate a warm and humid climate and under stong chemical weathering conditions. The values of V/(V+Ni), Cu/Zn and Ce/La suggest that organic-rich intervals of the Dawuba Formation accumulated under predominantly dysoxic conditions. The warm and humid climate is conducive to the flourishing of micropaleontology, and the high primary paleoproductivity and weakly reducing environment are conducive to the formation of organic-rich shale, forming high-quality reservoir source rock in the Dawuba Formation.